Preparation method of gel electrolyte with efficient flame-retardant characteristic
By preparing gel electrolyte with a composite skeleton with a crosslinked structure in lithium-ion batteries, the problem of traditional electrolytes being flammable under extreme conditions is solved, the flame retardancy and safety of the battery are significantly improved, and it has commercial application value.
Patent Information
- Application Number
- CN202411769765.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional organic liquid electrolytes are prone to fire or explosion under extreme conditions such as high temperature, short circuit or physical damage, causing the safety of lithium-ion battery systems to be threatened.
By reducing the amount of electrolyte and polymerizing the solidified electrolyte, a composite framework with a crosslinking structure is formed by using polymers of polyethylene oxide (PEO) or its analogs, solvents such as ethyl carbonate (EC), diethyl carbonate (DEC), methyl ethyl-2-oxo-1,3-dioxolane-4-ylmethyl phosphate (MEEP), and monomers and crosslinking agents such as lithium hexafluorophosphate (LiPF6), trifluoroethyl methacrylate (TFEM) and polyethylene glycol dimethacrylate (PEGDMA), to form a composite framework with a crosslinking structure, thereby preparing a highly efficient flame-retardant gel electrolyte.
It significantly improves the flame retardancy of lithium-ion batteries, reduces the fire risk of batteries under extreme conditions, and enhances the safety of the battery system. At the same time, it is simple in process and low in cost, and has commercial application value.
Smart Images

Figure CN119613636A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion battery electrolyte preparation, and in particular to a method for preparing a gel electrolyte with high-efficiency flame retardant properties. Background Art
[0002] In recent years, with the widespread use of electric vehicles and portable electronic devices, the safety issues of energy storage devices such as lithium-ion batteries have become increasingly prominent. Traditional organic electrolytes are prone to combustion under extreme conditions such as high temperature and short circuit, which seriously threatens the safety of battery systems. Therefore, the development of electrolyte materials with excellent flame retardant properties has become a hot topic in current research.
[0003] Traditionally, lithium-ion batteries rely mainly on organic liquid electrolytes to conduct ions, but these electrolytes are extremely prone to fire or even explosion under extreme conditions such as high temperature, short circuit or physical damage. This is because organic liquid electrolytes are mainly composed of flammable organic solvents. Once a short circuit occurs inside the battery or is affected by an external heat source, the electrolyte will quickly heat up and may reach its flash point or ignition point, causing thermal runaway of the battery, causing fire or explosion. In order to overcome this safety hazard, we began to explore and develop new electrolyte materials, among which gel electrolytes have attracted much attention due to their high flame retardancy, good ionic conductivity and easy molding. Gel electrolytes combine the high ionic conductivity of liquid electrolytes with the mechanical stability of solid electrolytes, which can inhibit the occurrence of internal short circuits in the battery to a certain extent and improve the safety of the battery. When preparing this highly flame-retardant gel electrolyte, a variety of strategies are adopted, such as adding fluorinated flame retardant additives to the electrolyte and using cross-linked polymers. These strategies are aimed at improving the thermal and chemical stability of the electrolyte, thereby enhancing its flame retardant properties.
[0004] The invention significantly improves the flame retardancy of the electrolyte by reducing the amount of electrolyte and polymerizing and solidifying the electrolyte. A preparation method of a gel electrolyte with high-efficiency flame retardancy is developed. The urgent need for safety in the field of lithium-ion batteries is met. The preparation method is easy to operate, simple in process, and has commercial application value. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing a gel electrolyte with high-efficiency flame retardant properties. The button cell assembled with the gel electrolyte of the present invention has significantly improved flame retardancy; the preparation method of the present invention is simple and reasonable, has low cost, and has commercial value.
[0006] The present invention adopts the following technical solutions:
[0007] A method for preparing a gel electrolyte with high efficiency flame retardant properties is prepared by the following steps:
[0008] (1) Adding a polymer, in particular a polymer selected from polyethylene oxide (PEO) or its analogs, into a clean and pre-treated container; adding a solvent into the container, wherein the solvent is a mixture of ethyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl-2-oxo-1,3-dioxolan-4-yl methyl phosphate (MEEP), and then stirring the solvent and polymer mixture, and appropriately heating the temperature of the solvent when necessary to promote complete dissolution of the polymer to form a uniform polymer solution.
[0009] (2) After the polymer solution is cooled to room temperature, lithium hexafluorophosphate (LiPF6) is slowly and evenly added, and stirring is continued until the lithium hexafluorophosphate is completely dissolved in the polymer solution to form a polymer solution containing lithium salt; trifluoroethyl methacrylate (TFEM) and polyethylene glycol dimethacrylate (PEGDMA) are sequentially added to the above polymer solution containing lithium salt as monomers and crosslinking agents, and they are ensured to be evenly dispersed in the solution by sufficient stirring to form a mixed reaction system.
[0010] (3) The mixed reaction system obtained in step (2) is transferred to a preset mold and allowed to stand at room temperature to allow trifluoroethyl methacrylate (TFEM) and polyethylene glycol dimethacrylate (PEGDMA) to undergo a polymerization reaction to form a composite skeleton with a cross-linked structure. The duration of this process is adjusted according to the ambient temperature and the activity of the polymerization initiator that may be added, and is usually between several hours and one day.
[0011] (4) After the polymerization reaction is completed, the composite skeleton in the mold is placed in an electrolyte for swelling treatment so that the electrolyte can fully penetrate into the pore structure of the composite skeleton to form a gel electrolyte. This swelling process lasts for at least 24 hours to ensure effective penetration of the electrolyte.
[0012] (5) Removal and drying: After swelling is completed, the gel electrolyte in the mold is removed and dried under controlled environmental conditions to remove excess solvent and moisture to ensure the stability and performance of the gel electrolyte. The dried gel electrolyte can be cut, trimmed, and processed as needed to meet the requirements of specific applications.
[0013] Preferably, in the mixture of EC, DEC and MEEP in step (1), the volume ratio of EC to DEC is 1:1, and the amount of MEEP added is 5% of the total volume to optimize the dissolution effect and electrolyte performance.
[0014] Preferably, the oxygen concentration in step (1) is ≥ 95% and remains consistent throughout the sintering process;
[0015] Preferably, in step (1), the solvent is heated to 50° C., which can significantly increase the dissolution rate of PEO and avoid the influence of high temperature on the subsequent polymerization reaction;
[0016] Preferably, the concentration of LiPF6 in step (2) is 0.1 mol / L to 1 mol / L to balance ion conductivity and electrolyte stability;
[0017] Preferably, the mass ratio of TFEM to PEGDMA in step (2) is 1:1 to obtain the best cross-linking effect;
[0018] Preferably, in step (3), the polymerization reaction time is 12 hours at room temperature (25° C.), which can obtain a better polymerization effect and a composite skeleton structure;
[0019] Preferably, the swelling process in step (3) is carried out at room temperature, but can be appropriately increased to 30° C. to 40° C. to accelerate the penetration rate of the electrolyte;
[0020] Preferably, the step (5) of drying in a vacuum drying oven at 40° C. for 24 hours can effectively remove excess solvent and moisture while avoiding damage to the gel electrolyte structure;
[0021] Preferably, the laser cutting technology used in step (5) can accurately cut the gel electrolyte as needed to meet the needs of different energy storage devices;
[0022] The beneficial effects of the present invention are:
[0023] (1) The present invention forms a solidified three-dimensional network structure of the gel electrolyte through polymerization technology, which limits the fluidity and volatility of the solvent. The gel electrolyte can form a more stable interface with the electrode material. Its solidified network structure helps to reduce the direct contact between the electrolyte and the electrode, reducing the probability of side reactions. In addition, the polymer components in the gel usually have high thermal stability and are not easy to burn. At the same time, the added flame retardant can further improve its safety performance. It provides a certain reference and basis for improving the efficient flame retardant performance of flame-retardant gel electrolyte materials in the future.
[0024] (2) The material preparation method of the present invention has a simple process and low cost, is suitable for industrial production, and has commercial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 These are pictures before and after heating polymerization in the process of preparing the flame-retardant gel electrolyte in Example 1 of the present invention;
[0026] Figure 2 This is a comparison picture of the combustion experiment of the flame-retardant gel electrolyte and the liquid electrolyte prepared in Example 1 of the present invention;
[0027] Figure 3 This is a temperature test experiment of a liquid electrolyte 314Ah battery cell prepared in Example 1 of the present invention;
[0028] Figure 4 This is a temperature test experiment of a 314Ah battery cell monomer of a gel electrolyte prepared in Example 1 of the present invention;
[0029] Figure 5 This is a thermal runaway voltage test experiment of a 314Ah battery cell of a liquid electrolyte prepared in Example 1 of the present invention;
[0030] Figure 6 This is a thermal runaway voltage test experiment of a 314Ah battery cell with a gel electrolyte prepared in Example 1 of the present invention; DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with embodiments and drawings.
[0032] Example 1
[0033] In combination with a specific example, a method for preparing a gel electrolyte with high efficiency flame retardant properties of the present invention is described, which is specifically prepared by the following steps:
[0034] (1) Adding a polymer, in particular a polymer selected from polyethylene oxide (PEO) or its analogs, into a clean and pre-treated container; adding a solvent into the container, wherein the solvent is a mixture of ethyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl-2-oxo-1,3-dioxolan-4-yl methyl phosphate (MEEP), then stirring the solvent and polymer mixture, and heating the solvent to 50° C. to promote complete dissolution of the polymer to form a uniform polymer solution.
[0035] (2) After the polymer solution is cooled to room temperature, 0.5 mol / l of lithium hexafluorophosphate (LiPF6) is slowly and evenly added, and stirring is continued until the lithium hexafluorophosphate is completely dissolved in the polymer solution to form a polymer solution containing lithium salt; trifluoroethyl methacrylate (TFEM) and polyethylene glycol dimethacrylate (PEGDMA) are sequentially added to the above polymer solution containing lithium salt as monomers and crosslinking agents, and they are ensured to be evenly dispersed in the solution by sufficient stirring to form a mixed reaction system.
[0036] (3) The mixed reaction system obtained in step (2) is transferred to a preset mold and allowed to stand at room temperature to allow trifluoroethyl methacrylate (TFEM) and polyethylene glycol dimethacrylate (PEGDMA) to undergo a polymerization reaction in a mass ratio of 1:1 to form a composite skeleton with a cross-linked structure. The reaction is carried out for 12 hours.
[0037] (4) After the polymerization reaction is completed, the composite skeleton in the mold is placed in an electrolyte for swelling treatment so that the electrolyte can fully penetrate into the pore structure of the composite skeleton to form a gel electrolyte. This swelling process lasts for at least 24 hours to ensure effective penetration of the electrolyte.
[0038] (5) Removal and drying: After swelling is completed, the gel electrolyte in the mold is removed and dried under controlled environmental conditions to remove excess solvent and moisture to ensure the stability and performance of the gel electrolyte. The dried gel electrolyte can be cut, trimmed, and processed as needed to meet the requirements of specific applications.
[0039] Example 2
[0040] The flame retardant gel electrolyte was prepared according to the steps of Example 1, except that in step 1, "the solvent heating temperature was increased from 50° C. to 70° C."; the other steps remained unchanged.
[0041] Example 3
[0042] The flame retardant gel electrolyte was prepared according to the steps of Example 1, except that in step 2, "the concentration of LiPF6 was increased from 0.5 mol / L to 2 mol / L."; the other steps remained unchanged.
[0043] Example 4
[0044] The flame retardant gel electrolyte was prepared according to the steps of Example 1, except that in step 3, "the polymerization reaction time was extended from 12 hours to 24 hours."; the other steps remained unchanged.
[0045] Example 5
[0046] The flame retardant gel electrolyte was prepared according to the steps of Example 1, except that in step 4, "the swelling temperature was increased from room temperature to 50° C."; the other steps remained unchanged.
[0047] Example 6
[0048] The flame retardant gel electrolyte was prepared according to the steps of Example 1, except that: before step 3, "0.5% ammonium persulfate was added to the mixture as an initiator."; the other steps remained unchanged.
[0049] The above is only a preferred embodiment of the present invention and does not limit the invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, other equivalent improvements can be made, which can achieve the purpose of the present invention and should be regarded as the protection scope of the present invention.
[0050] The flame retardant gel electrolyte prepared in Example 1 is characterized as follows:
[0051] Depend on Figure 1 It can be seen that TFEM monomer and PEGDMA crosslinker can transform liquid electrolyte into gel electrolyte through in situ polymerization process.
[0052] Depend on Figure 2 The combustion experiment shows that Figure 4 It can be seen from the combustion experiment that traditional liquid electrolytes are extremely flammable and release a large amount of heat during the combustion process; on the contrary, flame-retardant gel electrolytes always remain non-flammable after continuous exposure to a fire source.
[0053] Depend on Figure 3 and Figure 4 The temperature test experiment of the 314Ah battery cell shows that compared with the traditional liquid electrolyte, the overcharge temperature of the gel electrolyte cell is nearly 160°C lower.
[0054] Depend on Figure 5 and Figure 6 The thermal runaway voltage test experiment shows that compared with traditional liquid electrolytes, the thermal runaway voltage of the gel electrolyte 314Ah battery cell is lower, and the thermal runaway time is extended by half an hour.
Claims
1. A method for preparing a gel electrolyte with high efficiency flame retardant properties, characterized in that: The following steps are involved: (1) adding a polymer, in particular a polymer selected from polyethylene oxide (PEO) or its analogs, into a clean and pre-treated container; adding a solvent into the container, wherein the solvent is a mixture of ethyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl-2-oxo-1,3-dioxolan-4-yl methyl phosphate (MEEP), and then stirring the solvent and polymer mixture, and appropriately heating the temperature of the solvent when necessary to promote complete dissolution of the polymer to form a uniform polymer solution; (2) After the polymer solution is cooled to room temperature, lithium hexafluorophosphate (LiPF6) is slowly and evenly added, and stirring is continued until the lithium hexafluorophosphate is completely dissolved in the polymer solution to form a polymer solution containing lithium salt; trifluoroethyl methacrylate (TFEM) and polyethylene glycol dimethacrylate (PEGDMA) are sequentially added to the above polymer solution containing lithium salt as a monomer and a crosslinking agent, and they are ensured to be evenly dispersed in the solution by sufficient stirring to form a mixed reaction system; (3) transferring the mixed reaction system obtained in step (2) into a preset mold and allowing it to stand at room temperature to allow trifluoroethyl methacrylate (TFEM) and polyethylene glycol dimethacrylate (PEGDMA) to undergo a polymerization reaction to form a composite skeleton with a cross-linked structure. The duration of this process is adjusted according to the ambient temperature and the activity of a polymerization initiator that may be added, and is generally between several hours and one day. (4) After the polymerization reaction is completed, the composite skeleton in the mold is placed in an electrolyte for swelling treatment, so that the electrolyte fully penetrates into the pore structure of the composite skeleton to form a gel electrolyte. This swelling process lasts for at least 24 hours to ensure effective penetration of the electrolyte; (5) Removal and drying: After swelling is completed, the gel electrolyte in the mold is removed and dried under controlled environmental conditions to remove excess solvent and moisture to ensure the stability and performance of the gel electrolyte. The dried gel electrolyte can be cut, trimmed, and processed as needed to meet the requirements of specific applications.
2. The method for preparing a gel electrolyte with high efficiency flame retardant properties according to claim 1, characterized in that: In step (1), the temperature of the heated solvent is controlled within a range not exceeding the decomposition temperature of the polymer to avoid polymer degradation.
3. The method for preparing a gel electrolyte with high efficiency flame retardant properties according to claim 1, characterized in that: The ratio of trifluoroethyl methacrylate (TFEM) and polyethylene glycol dimethacrylate (PEGDMA) added in step (2) is adjusted according to the desired physical and chemical properties of the gel electrolyte.
4. The method for preparing a gel electrolyte with high efficiency flame retardant properties according to claim 1, characterized in that: The polymerization reaction in step (3) can be carried out under the condition of adding a suitable polymerization initiator and / or catalyst to promote the polymerization reaction.
5. The method for preparing a gel electrolyte with high efficiency flame retardant properties according to claim 1, characterized in that: The electrolyte used in step (2) is an organic solvent solution containing a lithium salt, wherein the lithium salt is selected from lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), etc., and the organic solvent is selected from ethyl carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), etc. or a mixture thereof.
6. The method for preparing a gel electrolyte with high efficiency flame retardant properties according to claim 1, characterized in that: The drying process in step (5) is carried out under vacuum or inert gas protection to prevent the gel electrolyte from reacting adversely with oxygen or moisture in the air during the drying process.
7. A method for preparing a gel electrolyte with high efficiency flame retardant properties according to any one of claims 1 to 6, characterized in that: The resulting gel electrolyte has excellent flame retardant properties and is suitable for use as an electrolyte in secondary batteries such as lithium ion batteries.
Citation Information
Cited By
Stable flame-retardant gel polymer for electrolyte
CN119875129A
A stable flame-retardant gel polymer for electrolyte
CN119875129B
Polyethylene oxide-alginate based semi-solid electrolytes with interpenetrating network structure and preparation and use thereof
CN122511994A